UJI DURABILITAS CAMPURAN AC-WC MENGGUNAKAN KOMBINASI LIMBAH PLASTIK DAN ABU SERABUT KELAPA SEBAGAI FILLER - Ondriani, Ondriani; Saleh, Sofyan M.; Isya, Muhammad (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract: The cause of damage and strength reductionon highway flexible pavement isthe low strength and durability on the wear layer. To cope withthis problem, it is necessary to add some particular additivethat can increase the asphalt concrete performance. One of the additional material that can be used are plastic. Stone ash, cement and fly ash has been commonly used as a filler in asphalt mixture. But these kind of filler was hard to get and the price were relatively expensive. The coconut fiber ash wich has a specific grafity greater than asphalt is expected to be one alternative. This research aims to determine the influence of plastic wastecombination substitution into the asphalt pen. 60/70 and the use of coconut fiber ash as filler on AC-WC mixture performance. The plastic used in this research is polyethylene terephthalate, polypropylene and polystyrene. The early stages of this research is to find the optimum asphalt content (OAC). After OAC obtained, then the specimens were mixed without and with the combination substitution of plastic waste as much as 2.7%; 4.7%; 6.7% against the weight of asphalt on OAC + 0.5% with and without the coconut fiber ash as a filler. The study results showed the use of plastic waste combination and the coconut fiber ash can not improve the durability value. The highest value of durability obtained at 4.7% combination substitution of plastic waste, it was 77.53%, While the lowest was in substitution of 6.7% plastic waste combination with 38.27% coconut fiber ash as a filler. The duration value of AC-WC mixture with plastic waste combination substitution and the use of coconut fiber ash filler did not meet the requirement that is 90%.Abstrak: Penyebab kerusakan dan penurunan kekuatan perkerasan lentur jalan raya adalah rendahnya kekuatan dan keawetan di dalam lapisan aus. Untuk menanggulangi hal ini dibutuhkan suatu bahan tambah yang dapat meningkatkan lapis aspal beton. Salah satu bahan tambah yang dapat di gunakan adalah plastik. Abu batu, semen dan fly ash sudah biasa digunakan sebagai filler dalam campuran aspal. Tetapi, jenis filler tersebut susah didapatkan dan harganya relatif mahal. Abu serabut kelapa yang memiliki berat jenis lebih besar dari aspal, diharapkan dapat menjadi alternatifnya. Penelitian ini bertujuan untuk mengetahui nilai durabilitas campuran AC-WC menggunakan kombinasi limbah plastik dan abu serabut kelapa. Plastik yang digunakan pada penelitian ini adalah Polyethylene Terephthalate, Polypropylenedan Polystyrene. Tahap awal penelitian ini adalah mencari kadar aspal optimum (KAO). Setelah KAO didapat kemudian dilakukan pembuatan benda uji tanpa dan dengan substitusi kombinasi limbah plastik sebesar 2,7%; 4,7%; 6;7% terhadap berat aspal pada KAO + 0,5% tanpa dan dengan abu serabut kelapa sebagai filler. Hasil penelitian menunjukkan penggunaan kombinasi limbah plastik tidak dapat meningkatkan nilai durabilitas. Nilai durabilitas tertinggi didapat pada substitusi kombinasi limbah plastik 4,7% yaitu 77,53% sedangkan yang terendah terdapat pada subtitusi kombinasi limbah plastik 6,7% dengan filler abu serabut kelapa yaitu 38,27%. Nilai Durabilitas campuran AC-WC dengan substitusi kombinasi limbah plastik dan penggunaan abu serabut kelapa sebagai filler tidak memenuhi syarat yaitu 90%.